WWII in HD. The air war. [videorecording (DVD)] - Jackson, Sammy; Lowe, Rob (A&E Television Networks, 2010)
The untold story of the American 8th Air Force's bloody battle to defeat the German Luftwaffe in the months leading up to D-Day. Told through the gripping, first person accounts of three American airmen and Stars & Stripes reporter Andy Rooney, this special showcases breathtaking aerial combat--original, color footage, never before seen by most Americans--of the B-17s Flying Fortresses, P-47 Thunderbolts and P-51 Mustangs on missions such as Regensburg, Schweinfurt and Berlin. Never-before-seen 8mm footage of the airmen on the bases, the devastation in Germany, and the Luftwaffe perspective is also highlighted. Flying 25,000 feet above the earth in oxygen-devoid air, and temperatures as low as 50 below zero, the 8th Air Force fought a war unlike anything ever before experienced. By the end, they would suffer more than 26,000 combat deaths--more than the US Marines lost in all of World War II.